Treatment outcomes among tuberculosis patients at an urban health centre, Goa, India- eight year retrospective record based study - Akarkar, Nikhil S.; Pradhan, Saili S.; Ferreira, A. M. (International Journal Of Community Medicine And Public Health, 2017)
Background: India contributes the highest TB burden globally and DOTS being the key strategy of RNTCP needs evaluation. The objective of this study was to assess treatment outcomes in TB patients on DOTS in terms of success rates in new and retreatment cases. Methods: Retrospective record based study was conducted at urban health centre, Santa Cruz Goa, India including 135 TB cases registered from January 2008 to January 2016 for DOTS. Data on treatment outcomes was analysed using appropriate statistical methods and percentages were calculated. Results: Out of total 135 TB cases, 64.4% had pulmonary while 35.6% had extra-pulmonary TB. Percentage of new cases was 84.4% whereas 15.6% were retreatment cases. Success rate (cure rate plus treatment completion rate) for new cases was 84.2% and for retreatment cases was 76.2% while the overall success rate was 83%. Conclusions: Successful treatment outcome was lower compared to the RNTCP norm.